The Influence of the Problem-Based Learning Model on the Persuasive Writing Ability - Lestusen, Irfan; Maspaitella, Martha (Universitas Pattimura, 2025)
The Problem-Based Learning (PBL) model is a learning paradigm that aims to engage students in critical thinking through the presentation of authentic problems and enhance their learning capabilities. This study aims to examine the influence of the PBL model on the persuasive writing ability of grade VIII students at MTs Negeri 6 Central Maluku. This research employed a quantitative experimental method with a quasi-experimental design. The research procedure was conducted using data collection methods including observation, interviews, learning processes, questionnaires, and documentation. The research population consisted of all grade VIII students at MTs Negeri 6 Central Maluku, with a sample of 60 students divided into experimental class (30 students) and control class (30 students). The research instruments comprised persuasive writing ability tests, observation sheets, and learning motivation questionnaires. Data were analyzed using paired sample t-tests with SPSS 25.0 software. The results showed a significant difference in persuasive writing ability between the experimental and control classes. The experimental class implementing the PBL model achieved an average post-test score of 52.5, while the control class using conventional methods achieved an average of 48.8. The t-test results showed a Sig. (2-tailed) value of 0.005 < 0.05, thus H₀ was rejected and Hₐ was accepted. These findings confirm that the PBL model significantly influences the improvement of students' persuasive writing ability by enhancing active engagement, critical thinking skills, and argumentation competencies in Indonesian language learning.